2022
DOI: 10.1051/0004-6361/202243850
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of free-floating planet candidates in Upper Scorpius and Ophiuchus

Abstract: Context.A rich population of low-mass brown dwarfs and isolated planetary mass objects has been reported in the Upper Scorpius and Ophiuchus star-forming complex. Aims. We investigate the membership, nature, and properties of 17 of these isolated planetary mass candidates using low-resolution near-infrared spectra. Methods. We investigated the membership by looking for evidence of their youth using four diagnostics: the slope of the continuum between the J and Ks band, the H cont , and the TLI-g gravity-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To break this degeneracy, it is fundamental to know the age of the FFP or to carry spectroscopic observations that can detect youth indicators on the spectra. Bouy et al (2022) observed 17 of the FPPs identified by Miret-Roig et al (2022a) with low-resolution near-infrared spectra obtained with SWIMS at the 8m telescope Subaru and EMIR at the 10m telescope GTC. They were able to confirm 16 of the 17 observed targets as young ultracool objects based on several spectroscopic criteria.…”
Section: Spectroscopic Confirmationmentioning
confidence: 81%
See 1 more Smart Citation
“…To break this degeneracy, it is fundamental to know the age of the FFP or to carry spectroscopic observations that can detect youth indicators on the spectra. Bouy et al (2022) observed 17 of the FPPs identified by Miret-Roig et al (2022a) with low-resolution near-infrared spectra obtained with SWIMS at the 8m telescope Subaru and EMIR at the 10m telescope GTC. They were able to confirm 16 of the 17 observed targets as young ultracool objects based on several spectroscopic criteria.…”
Section: Spectroscopic Confirmationmentioning
confidence: 81%
“…Up to now, the community has identified a few hundred candidates but only tens have been confirmed with spectroscopy. I have reviewed the last advances in the detection of FFPs and, in particular, the recent identification of 70-170 FFPs in Upper Scorpius and Ophiuchus, 16 of which have been confirmed with spectroscopy, measuring a very low contamination rate of < 6% on the initial sample (Miret-Roig et al, 2022a;Bouy et al, 2022). This sample constitutes the largest population of young co-eval FFPs to date and is an excellent benchmark to investigate their formation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…As examined in detail in Chabrier et al (2014b, and references therein), this semantic definition has no robust scientific justification and brings a lot of confusion. The observations of Miret-Roig et al (2022), confirmed by Bouy et al (2022), rather suggest an excess of low-mass BDs compared with the C05 IMF. These determinations, however, are subject to both observational and theoretical uncertainties and must be confirmed unambiguously.…”
Section: Summary Of the Comparisons With The Observations And Consequ...mentioning
confidence: 79%
“…To break this degeneracy, it is fundamental to know the age of the FFP or to carry spectroscopic observations that can detect youth indicators on the spectra. Bouy et al (2022) observed 17 of the FPPs identified by Miret-Roig et al (2022a) with low-resolution near-infrared spectra obtained with SWIMS at the 8 m telescope Subaru and EMIR at the 10 m telescope GTC. They were able to confirm 16 of the 17 observed targets as young ultracool objects based on several spectroscopic criteria.…”
Section: Spectroscopic Confirmationmentioning
confidence: 88%